Best Answer

It can't be solved because it is not an equation but the given expression can be simplified to -2x-16

More answers

The question contains an expression but not an equation nor inequality. An expression cannot be solved.

Q: How do you solve -2(x plus 3) -10?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

4x-3+2x-x = 10 Collect the like terms; 5x-3 = 10 5x = 13 x = 13/5

2x+3 = 7 2x = 7-3 2x = 4 x = 2

Simplist form of 2x plus 3-10 is 2x-7.

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

Related questions

5x+7 = 2x-3 5x-2x = -3-7 3x = -10 x = -10/3

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

4x-3+2x-x = 10 Collect the like terms; 5x-3 = 10 5x = 13 x = 13/5

3

2x+3 = 7 2x = 7-3 2x = 4 x = 2

Simplist form of 2x plus 3-10 is 2x-7.

2x+3 = -11 2x = -11-3 2x = -14 x = -7

2x - 4 = -10 2x = -10 +4 2x = -6 x = -3

7 plus 7x--2x plus 3 is: 7 + 7x + 2x + 3 = 0 9x + 10 = 0 9x = -10 x = -10/9 = -1 1/9

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

3x+4 = 2x-3 3x-2x = -3-4 x = -7